Analisis Faktor Faktor Yang Mempengaruhi Cycle Time pada PT.Cakrawala Nusa Bahari - Dian W., Dany; Rusmiyanto, Dedy (Politeknik Bumi Akpelni, 2024)
More than 90% of the coal produced in Indonesia comes from Kalimantan, the country's coal production hub. Only about 51% of national coal reserves are found in Kalimantan; other regions of the country, particularly Sumatra, have significant coal reserves. Coal and other mineral resources in large quantities, including petroleum, are stored underground in the interior of the earth. This study is expected to see and learn about several variables of Waiting Time, Loading and Unloading Productivity and Ship Scheduling and whether it affects Cycle time at PT. Nusa Bahari Skyline. The population of this study is Clients who use the services of PT. Cakrawala Nusa Bahari with a sample of 100 respondents with sampling techniques Non probability sampling type of incidental sampling by distributing questionnaires and the data obtained are processed using quantitative analysis using SPSS software. The study found that waiting time had a good and large influence on cycle time. The results of multiple linear regression equations prove that ship scheduling has a positive and large effect on cycle time (table values of 2.641 > 1.98472). The results of multiple linear regression equations prove that loading and unloading bring benefits and are great for cycle time (calculated value of 2.777 > table value of 1.98472).